2019
DOI: 10.1007/s00253-019-09806-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a solvent-tolerant haloarchaeal (R)-selective transaminase isolated from a Triassic period salt mine

Abstract: Transaminase enzymes (TAms) are becoming increasingly valuable in the chemist’s toolbox as a biocatalytic route to chiral amines. Despite high profile successes, the lack of ( R )-selective TAms and robustness under harsh industrial conditions continue to prove problematic. Herein, we report the isolation of the first haloarchaeal TAm (BC61-TAm) to be characterised for the purposes of pharmaceutical biocatalysis. BC61-TAm is an ( R )-selective enzyme, cloned from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Recent metagenomic mining from a hypersaline environment also yielded a functional TAm, KMG-TAm4 (Kelly et al 2018b). In this case, however, the enzyme produced did not exhibit a halophilic or halotolerant activity profile, as had been observed in previous enzymes characterized from cultured microbes from the same source (Kelly et al 2017(Kelly et al , 2019a. This may be due to the adaptive mechanisms employed by some halophiles, where the organism as a whole is adapted to hypersaline environments by excluding salt from the cell, meaning intracellular enzymes do not themselves need to be salt-adapted.…”
Section: Sequence-driven Metagenomicsmentioning
confidence: 50%
See 1 more Smart Citation
“…Recent metagenomic mining from a hypersaline environment also yielded a functional TAm, KMG-TAm4 (Kelly et al 2018b). In this case, however, the enzyme produced did not exhibit a halophilic or halotolerant activity profile, as had been observed in previous enzymes characterized from cultured microbes from the same source (Kelly et al 2017(Kelly et al , 2019a. This may be due to the adaptive mechanisms employed by some halophiles, where the organism as a whole is adapted to hypersaline environments by excluding salt from the cell, meaning intracellular enzymes do not themselves need to be salt-adapted.…”
Section: Sequence-driven Metagenomicsmentioning
confidence: 50%
“…Gao et al (2017) characterized an Rselective TAm from the fungus Fusarium oxysporum (Gao et al 2017), while the first haloarchaeal TAm characterized for use in biocatalysis (BC61-TAm) was isolated from the genome of Halorubrum sp. CSM-61 (Kelly et al 2019a). These examples reinforce the benefit of mining genomes from previously untapped or extreme environments, with both yielding relatively scarce and valuable R-selective TAms.…”
Section: Homologous Sequence Searchingmentioning
confidence: 76%
“…Streptomyces spp. are usually saprophytic soil-dwelling aerobic filamentous bacteria playing a crucial role in soil ecology by effectively hydrolyzing a wide range of polysaccharides (cellulose, chitin, xylan, and agar) and other natural macromolecules [6]. This biodegradation efficiency is based on the secretion of potent hydrolases (enzymes classified as EC 3 in the EC number classification) such as cellulases, lipases, proteases, xylanases, and cutinases, while other enzymes of environmental and industrial importance have also been identified from this genus [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that ω-TA is well tolerated by organic solvents and the results are superior to that of a solvent-tolerant haloarchaeal (R)-selective transaminase isolated from a Triassic Period salt mine [37].…”
Section: Purification and Identification Of Recombinant ω-Tamentioning
confidence: 94%